Temporal Trends of Obesity Among Nebraska Adults: EMR Data Shows a More Rapid Increase Than Projected - Elizabeth M. Gibson; Jenenne A. Geske; Birgit N. Khandalavala (SAGE Publishing, 2024)
Introduction/Objectives: Obesity data is typically obtained from national population surveys, while the use of more accurate electronic medical record (EMR) data is underutilized. The objective of this study is to calculate current obesity prevalence and weight trends using EMR data and compare the results to prior survey-based obesity prevalence projections for the state. Methods: This retrospective study analyzed Body Mass Index (BMI) from deidentified EMR data from 16,491 adult patients in urban midwestern primary care clinics between January 2017 and October 2021 for obesity prevalence and weight trajectories, stratified by age and gender. Results: There was a large discrepancy between the survey-based self-reported rates of obesity (35.5%) and those calculated from baseline EMR data (47.6%), along with a smaller discrepancy in females (47.9%) compared to males (47.2%). Young adults aged 20 to 29 years showed a larger increase in BMI over time compared to other age groups Conclusions: EMR-derived data indicates a prevalence of obesity greater than projections that have been based on self-reported survey data as well as higher weight trends than projected for this midwestern state. As evident from our study, cohorts such as at-risk young adults with a more rapid weight gain trajectory should be prioritized for enhanced obesity management.